Ocorrência de câncer na região oeste do Paraná: análise a partir da ocupação e exposição a agrotóxicos - Ruths, Jéssica Cristina (2018)
The pesticides affect human health due to its intrinsic toxicity, producing effects that vary according to the active principle, the absorbed dose and the form of exposure. Among the various effects of these substances stands out the association with the occurrence of cancer. Thus, the objective was to analyze the association between exposure to pesticides and the occurrence of cancer in the populations of the municipalities of Anahy and Vera Cruz do Oeste, Paraná. Two studies were developed that gave origin to two articles. In the first one, a documentary, cross-sectional and quantitative study was developed. Data collection was performed in the Hospital Registry of Cancer (Integrator RHC) system, the time period selected for analysis was from 2012 to 2014. The variables selected were occupation, primary location of the neoplasm and the municipality of residence. For comparisons between the categories we used the Chi-square test for K proportions, followed by the Marascuilo procedure. In the second, a field survey was carried out in the municipalities of Anahy and Vera Cruz do Oeste, through the application of a semi-structured interview script, with individuals who had or had cancer and were exposed to pesticides at some point in their previous life. Data collection took place from October 2016 to April 2017. Quantitative data were analyzed based on descriptive statistics using Microsoft Excel Software, while qualitative data were used to counter or reinforce quantitative data. The first study identified a statistically significant difference for neoplasms of lip, oral cavity and pharynx, with a greater proportion of occurrence among military, police, military and firefighters; for melanomas and other skin cancers, with the highest proportion among agricultural, forestry and fishing workers; for breast neoplasms, with a higher proportion among administrative service workers; for female genital organ neoplasms, where the largest was between male and female administrative services and male genital organs, with a higher proportion of military, police, military and firefighters. In the second study the results showed that 46.88% of the individuals who had or had cancer in Anahy and 32% in Vera Cruz do Oeste were exposed to pesticides prior to the diagnosis of cancer. There was a predominance of elderly individuals, farmers and low schooling. The main activities were the harvesting, planting, carpiring and the application of agrochemicals. Temporality was, in general, expressive, 56.42% of the population was exposed for more than 30 years. It was identified contact with 19 formulas of pesticides, of these, 47.36% do not have release of use, since they were considered harmful to human and environmental health. There was a prevalence of skin, prostate and breast cancers, respectively. The present study poses that occupational exposure may contribute to the illness of specific groups and that the results do not rule out the influence of exposure to pesticides in the occurrence of cancer.